Reverse Engineering the Anthropocene: Can Human Consciousness Change Reality? - Rhule, Author: Ketziah; S. Javaheri, Editor: Skye (The Oracle, 2021)
A greater awareness of the Anthropocene brings to the surface critical questions about the nature of human reality or, more specifically, the role human consciousness plays in the formation of the physical world, its construction, functionality, and interactivity. This paper uses a dialogical correlation of Aristotle, Max Planck and Dean Radin in order to first, formulate parameters of reality formation and the active role of consciousness as part of this process; and, second, consider the possibility that humanity’s consciousness can be trained to effect deliberate change in the material world. This paper argues that one of the ways to understand the Anthropocene is through the idea that reality is “running away” from us because we are not aware of the role our consciousness plays in the process of reality formation.